Plant-based amyloids from food waste for removal of heavy metals from contaminated water - Soon, Wei Long (2022)
Water pollution is one of the major global threats brought about by industrial, agricultural, and any other anthropogenic activity. Heavy metals represent a large group of water pollutants that can accumulate in the human body, causing cancer and mutagenic diseases. Technologies currently used to treat polluted wastewaters of heavy metals employ chemical, ion-exchange, and membrane purification methods. However, these techniques are energy-intensive due to high pressure and power requirements for membrane-based technologies, or highly selective, as in ion-exchange resins, making drinking water less affordable in developing countries. In this study, plant amyloid-carbon membranes consisting of sunflower and peanut amyloid fibrils were fabricated through a green and sustainable process and were used to remove toxic heavy metal pollutants to drinkable standards with negligible energy consumption. Protein-rich sunflower and peanut meals serve as low-cost raw materials, from which proteins were extracted, isolated, and self-assembled into functional amyloid fibrils for heavy metal removal. These amyloid fibrils were incorporated into hybrid carbon/amyloid membranes and used to filer Pt-, Cr-, and Pb-containing water to produce water of drinkable standards containing < 10 ppb heavy metals. This process can easily be upscaled due to its simplicity and minimal use of chemical reagents, pointing towards the future of low-cost yet efficient water treatment technologies.